Innocence of 1980s Malaysia captured in patriotic songs - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
AUGUST is just around the corner, which means the Jalur Gemilang will make its annual appearance in the shopping centres, taxis, and offices to usher in Hari Merdeka this month and Malaysia Day on September 16.